NARRATIVE REVIEW: MANAJEMEN SYSTEMATIC RISK DAN UNSYSTEMATIC RISK UNTUK MENINGKATKAN EXPECTED RETURN - Sitti Mukarromah; Ibnu Suryo; Peni Febrianita Meliana (LP3M, 2023)
The aim of this research is to explain the extent of the influence of systematic risk and unsystematic risk in an effort to increase the company's expected return. This research is a type of descriptive research through literature review. The data collection technique consists of collecting archival data, namely 11 published articles or national journals, then analyzing their contents. Based on several research results, systematic risk has a positive and significant influence on expected returns, this is because shares are influenced by systematic factors such as: war, inflation, recession and high interest rates, so risk cannot be eliminated by diversification. Meanwhile, several research results show that unsystematic risk has varying significance on expected profits. Investors are advised to consider this risk and diversify by investing their capital in several stocks that will form a portfolio. The results of the literature review show that companies need to pay attention to systematic risk and unsystematic risk management as an effort to increase the company's expected return